Perencanaan Penyediaan Fasilitas Parkir Pada Pasar Palengaan Kabupaten Pamekasan - Zabadi, Fairus; Fatoni, Ahmad (Sekolah Tinggi Teknologi Dumai, 2024)
The provision of parking facilities at the Palengaan market shopping center gives rise to a fairly large parking generation, then the problem that arises from this large generation is the demand for parking spaces that are effective and can accommodate and provide comfort for visitors. This is greatly influenced by the use pattern of the parking area in question, the location of the parking area. So, when handling parking problems, regulations regarding land use patterns must also be followed which are adjusted to the detailed plans for providing vehicle parking facilities. Therefore, in this research, planning will be carried out regarding the availability of parking spaces and vehicle parking systems for visitors to the Palengaan market and will focus on providing parking capacity and how to optimize the parking system that does not yet exist. From the results of the analysis of the characteristics of vehicle parking at the Palengaan market, it can be seen that the area of parking requirement at the Palengaan market is 215,69 units. It is better to build a parking lot at the Palengaan market because the large market really needs a parking area so that it can complete the facilities at the Palengaan market.